Optimal Estimation of Solar Radiation on Flat Surfaces for the Design of Energy Systems using Artificial Neural Networks - Huerta F.A.C. (2019)
ACKNOWLEDGMENT Franklin Alfredo Cabezas Huerta would like to thank the support provided by the CER – UNI and also express special thanks to the National Fund for Scientific and Technological Development (FONDECYT – PERU) for the scholarship awarded to do PhD studies in Science with mention in Energetics in the National University of Engineering.